Determination of aflatoxin M1 in milk by ultra-performance liquid chromatography and fluorimetric detection combined with large volume flow cell - WANG Junlin; CAI Zengxuan; REN Yiping (浙江大学学报. 农业与生命科学版)
Aflatoxins (AFT), whose basic structure is composed of difuran and coumarin, have 17 kinds of derivatives including B1, B2, G1, G2, M1, M2, etc. AFT M1 was firstly separated from milk. AFT M1 and AFT M2 were the derivatives of AFT B1 and AFT B2 through the animal metabolism. Especially, AFT B1 and AFT M1 have been defined as a category A and 2B carcinogen by the International Agency for Research on Cancer (IARC) from World Health Organization (WHO) in 1993, respectively. Moreover, AFT B1 and AFT M1 are regarded as strong carcinogens, the carcinogenic mechanism of which is achieved via affecting the pericellular membrane, inhibiting the synthesis of RNA and interfering the inductive style of specific enzymes. In December 2011, the General Administration of Quality Supervision, Inspection and Quarantine of the People's Republic of China (AQSIQ) announced the selective examination results of 200 kinds of liquid milk products. The aflatoxin M1 in parts of milk products were over ranging the maximum residue limits (MRLs) of M1 in milk and milk products, of which the maximum superscalar were 140% exceeded. Moreover, the contents of aflatoxin M1 were found exceeded in milk powder again in July 2012. The method used now was to first heat the milk and milk products in water bath, then samples were clean-up and concentrated by immunoaffinity column after filtered or centrifuged. In this method, no clear sample solutions were obtained, when passing through the immunoaffinity column, sometimes the immunoaffinity column would be blocked, and the recovery would not in expectation. So a better method was needed for determinating the aflatoxin M1 in milk and milk products.The present study developed an improved analytical method for the fast determination of aflatoxin M1 in milk and milk products by ultra-performance liquid chromatography (UPLC) combined with large volume flow cell fluorescence detection (FLD). The milk sample was extracted by acetonitrile, and the ratio of the milk sample to acetonitrile was 1 to 2.5 in mass to volume. Then, the sample was extracted by vortex and ultrasound assisted liquidliquid extraction (ULLE), and was cleaned-up and concentrated by aflatoxin M1 immunoaffinity column. The analyte was separated by UPLC BEH C18 column (100 mm×2.1 mm, 1.7 μm), and was eluted with acetonitrile-methanol (50∶50) and pure water.The results showed that the limit of quantitation (LOQ) of aflatoxin M 1 was 0.03 μg/kg, which was lower than the national criteria on determination of the minimum level of aflatoxin M 1 in milk and milk products. Meanwhile, high correlation coefficient (R2>0.999) was obtained within linear range from 0.06 to 1.2 μg/kg, and reasonable recoveries (81.95% -94.20%) were in different spike level. In addition, acetonitrile could effectively precipitate protein in milk during the pretreatment to obtain clear extraction which could rapidly pass through immunoaffinity column only by gravity. When using the large volume flow cell, the sensitivity was increased, which was three times than the standard flow cell. The results obtained from this method were similar to the classical method.In conclusion, this quantitative method has many advantages including simple pretreatment, rapid determination and high sensitivity, which can be applied to the determination and quantification of aflatoxin M 1 in milk sample.